1996
DOI: 10.1172/jci118630
|View full text |Cite
|
Sign up to set email alerts
|

The subtype-2 (AT2) angiotensin receptor regulates renal cyclic guanosine 3', 5'-monophosphate and AT1 receptor-mediated prostaglandin E2 production in conscious rats.

Abstract: The renal effects of angiotensin II(AII) are attributed to AT 1 receptors. In contrast, the function of renal AT 2 receptors is unknown. Using a microdialysis technique, we monitored changes in renal interstitial fluid (RIF) prostaglandin E 2 (PGE 2 ) and cyclic guanosine 3 Ј , 5 Ј -monophosphate (cGMP) in response to dietary sodium (Na) depletion alone, or Na depletion or normal Na diet combined with the AT 1 receptor blocker, Losartan, the AT 2 receptor blocker, PD 123319 (PD), or angiotensin II, individuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
235
4
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(256 citation statements)
references
References 18 publications
(20 reference statements)
14
235
4
1
Order By: Relevance
“…The distribution of renal AT 2 receptor subtypes has not been precisely determined with the exception of the apical receptor on proximal tubular epithelial cells and glomerular endothelial cells (1,19). Signaling linked to AT 2 receptor includes activation of MAPK phosphatase, NO, guanylate cyclase, and PLA 2 (1,20,21,22). The current studies broaden our understanding of AT 2 -mediated signaling and document modulation of p21ras in proximal tubular epithelium.…”
Section: Discussionmentioning
confidence: 81%
“…The distribution of renal AT 2 receptor subtypes has not been precisely determined with the exception of the apical receptor on proximal tubular epithelial cells and glomerular endothelial cells (1,19). Signaling linked to AT 2 receptor includes activation of MAPK phosphatase, NO, guanylate cyclase, and PLA 2 (1,20,21,22). The current studies broaden our understanding of AT 2 -mediated signaling and document modulation of p21ras in proximal tubular epithelium.…”
Section: Discussionmentioning
confidence: 81%
“…The mechanism whereby brain AT 2 receptor mediates vasodepressor response to footshocks may be explained through the release of substances such as bradykinin or NO. 40 AT 2 receptor may exert its vasodepressor effect by stimulating local release of nitric oxide either directly or via kinins 13,41 which together with blockade of the AT 1 receptor may have an vasodepressor effect.…”
Section: Discussionmentioning
confidence: 99%
“…40 Indeed, it has been shown that vasorelaxation in several experimental preparations is blocked by inhibitors of methylene blue, a soluble guanylyl cyclase inhibitor, suggesting a role for nitric oxide-guanylyl cyclase system. 11,42 It could be that the angiotensin AT 2 receptor exerts its haemodynamics effects by stimulating local release of nitric oxide either directly or via kinins 13,14,41 which together with the blockade of the angiotensin AT 1 receptor may have an vasodilator effect. It has been reported that in cultured bovine aortic endothelial cells, angiotensin II induces a sixto seven-fold increase in the release of cGMP; this effect was abolished by a kinin antagonist and a nitric oxide synthesis inhibitor and markedly inhibited by an angiotensin AT 2 receptor antagonist, but only marginally inhibited by an angiotensin AT 1 receptor antagonist, 14 suggesting that angiotensinstimulated release of nitric oxide is predominantly due to stimulation of the angiotensin AT 2 receptor and may lead to an increase in the effect of kinins, stimulation of nitric oxide and increased cGMP formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that stimulation of the AT 2 receptor increases the production of bradykinin, PGE 2 and NO, leading to arteriolar vasodilation and suppression of cell growth and proliferation. [40][41][42][43] Therefore, the inability of ARBs to prevent kinin degradation in contradistinction to ACE inhibitors is compensated by their ability to increase kinin production through the AT 2 receptor. Although these actions are shared by all ARBs, telmisartan has the additional advantage of being longer acting and more efficacious with respect to its antihypertensive effects and to effectively suppress the rise of blood pressure during the early hours of the morning when it is needed the most.…”
Section: Angiotensin Receptor Blockers Vs Angiotensin-converting Enzymentioning
confidence: 99%